Aplicação do método iterativo do gradiente hidráulico modificado pelo método de busca para a calibração da condutividade hidráulica horizontal de aquífero da bacia sedimentar do Araripe com avaliação do período de seca 2010-2016 - Sá, Pétrus Eduardo Feliciano de (2018)
This work aims to perform the modeling of the aquifer groundwater flow through co mputer simulation using the Hydraulic Gradient Iterative Method (MIGH), modified by the search method in the calibration process. The method was tested in a hypothetical example and in a real example corresponding to an aquifer that covers the urban area o f the municipality of Crato - CE, in the Araripe Sedimentary Basin, allowing the evaluation of the effects related to the drought period 2010 - 2016. Underground flow modeling was performed using the UFC - FLOW extension, which operates in association with gvS IG, a geoprocessing software used to facilitate the elaboration of the model input matrices. The calibration of the horizontal hydraulic conductivity parameter was successfully obtained through simulation of the model and the fixation of hydraulic loads ob served and measured in the field. The satisfactory results in the calibration of the hydraulic conductivity attest to the validity of the MIGH, but the search method implemented in association with the calibration presented partially satisfactory results, in which for the hypothetical case studied, the method worked presenting a small error, however, for the the real case, in which the model has non - homogeneous conductivities, presented significant differences as the initial load varied, demonstrating the n eed to improve the search method. The results obtained also show the potential of the UFC - FLOW software, supported by a Geographic Information System (GIS) for underground flow simulation and aquifer modeling, as well as the subsequent solution of the hydr odynamic parameter calibration problem based on MIGH. The analysis of the change in the static level of the aquifer in the region caused by the drought period between 2010 and 2016 revealed an average decrease of more than two meters, showing that the rech arge was insufficient during the dry season and that measures should be taken to preserve the in these critical times